To the question of improving the system object monitoring of subsurface conditions at the enterprises of the state corporation «Rosatom» - T. I. Klimova; E. B. Sevtinova; L. G. Chertkov; A. D. Palagushin; M. V. Udalaya (Известия высших учебных заведений: Геология и разведка, 2015)
A specialized system-based monitoring of the subsoil (AMSN) is being created for the first time in the state corporation «Rosatom». The main task is a development of a unified methodical approach. The results of a survey of the system object monitoring of the subsoil at the enterprises of the state Corporation «Rosatom» (51) have been summarized. The most frequently occurring methodological errors in the formation of observational networks and monitoring the condition of groundwater, which lead to unreliable results of the monitoring, have been analyzed for the first time. Criteria has been developed to improve the reliability of the monitoring results, and the scale of the assessment of the existing systems of object monitoring of the subsoil was given by the combination of the following factors: the necessary and sufficient number of observation points; placement of observation points relative to a potential or immediate source of pollution and general geological and hydrogeological conditions; design and technical condition of observation points; compliance to the hydrogeological practice methods of sampling, storage, sample preparation for laboratory studies; compliance of the equipment base and laboratory techniques regulatory requirements for range and accuracy of measurements; methods of processing, stockpiling and storage of results. The design of observation wells has been developed for various types of permeability of water-saturated enclosing rocks. The basic requirements have been developed for the establishment and operation of the observation network, for the method of sampling, for sample preparation, for laboratory equipment and measurement of radiation of groundwater.